Influence of Hydroethanolic Mixtures on Characteristics of Bougainvillea glabra Bracts Dyes: Textile Dyeing, Fastness Properties and Application as Indicator in Acid-Base Titration - Oyeleke, Gboyega Oluwaseun; Ajao, Funmilola Dupeola; Oyeleke, Olusola Olamide (FUDMA Journal of Sciences, 2026)
The study investigated the extraction, characterization and dyeing potential of natural dyes obtained from Bougainvillea glabra bracts using different solvent systems. Fresh plant materials were extracted using maceration techniques with three solvent systems: distilled water, 90% and 10% ethanol. The resulting extracts were analyzed using UV-Visible and Fourier Transform Infrared (FTIR) spectroscopy to determine their chromophoric and functional group compositions. The UV-Vis spectra showed strong absorption peaks between 200-400 nm, indicating the presence of phenolic and flavonoid compounds, while FTIR results confirmed hydroxyl, alkenyl, alkyl and carbonyl groups responsible for dyeing characteristics. Cotton fabrics dyed with the extracts were evaluated for light, washing, rubbing, ironing and perspiration fastness. The 90% ethanolic dye extract demonstrated the highest colour intensity and fastness properties, followed by the 10% ethanol and aqueous dye extracts respectively. The use of the extracts as indicators in acid-base titration produced a change in colour which is an indication that it can be used as alternative to common synthetic indicators. The results revealed that solvent polarity significantly affects the quality of pigment and dye-fiber affinity. Therefore, B. glabra dye extracts presented a viable eco-friendly alternative to synthetic colourants for textile coloration and other industrial applications.